Fenomena Pergeseran Mahar dalam Tradisi Adat Sabu : Studi Fenomenologi di Kota Kupang - Merrie CH Nawa; Aloysius Liliweri; Hotlief Nope (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study applies Edmund Husserl’s phenomenological approach to explore the transformation of dowry practices in the Sabu tradition. The dowry, once represented by kenoto a container of areca nut and betel leaf with sacred symbolic value has shifted to modern forms such as cash, fruits, or packaged food. The focus is to understand the subjective responses of the Sabu diaspora in Kupang City toward these cultural changes. Data were gathered through in-depth interviews and observations, then analyzed using phenomenological reduction to uncover the essence of lived experience. Findings reveal a dilemma between preserving the symbolic meaning of kenoto and adapting to the demands of modern life. Economic conditions, education, religion, and media exposure emerge as significant factors influencing this shift. Some community members reject the change, arguing that it diminishes sacred values and weakens communal ties. Others perceive it as a necessary adjustment to contemporary realities, ensuring that the tradition remains relevant without losing its social function. The study concludes that the transformation of dowry is not only a material change but also a negotiation of values between tradition and modernity. This reflects the ongoing reconstruction of cultural identity among the Sabu people, especially in the diaspora context. The research contributes to existing literature by emphasizing subjective experiences rather than purely legal, religious, or sociological perspectives. By highlighting how the community interprets these transformations, the study enriches scholarly discussions of cultural shifts and underscores the dynamics of consciousness and identity in local communities navigating modernization.